Late-onset Pompe disease - literature review and summary of current knowledge - Karolina Jaskuła; Konrad Merkisz; Sylwia Nemeczek; Klaudia Walczak; Jakub Grzybowski; Agnieszka Marciniak; Władysław Orłowski; Natalia Grzywna; Patrycja Walczak; Weronika Salasa (Nicolaus Copernicus University in Toruń, 2023)
Introduction: Pompe disease is a glycogen storage disorder caused by the deficient activity of the lysosomal enzyme acid α-glucosidase (GAA). Mutations in the GAA gene lead to the accumulation of glycogen in different organs. In a late-onset form (late-onset Pompe disease), the disease is characterized by slow, progressive proximal limb and respiratory muscle weakness. The diagnosis is based on a low level of GAA either in the muscle biopsy or in the leucocytes. LOPD is treated with enzyme replacement therapy (ERT). Purpose: Summary of currently knowladge about Late-onset Pompe disease - characteristic, diagnosis and treatment. Methods: A review of literature available in the PubMed database and Google Scholar. by searching for keywords: Pompe disease, Late-onset Pompe disease, LOPD, alglucosidase- α. Results: The diagnosis of late-onset Pompe disease can often be difficult. It is a very rare disease and the clinical presentation is similar to other neuromuscular disorders, such as Duchenne and Backer muscular dystrophies, glycogenosis or autoimmune or mitochondrial myopathies and others. Despite available specific enzyme replacement therapy LOPD is progressive. Patients require support from a multidisciplinary team of specialists, including care from neurologists, pulmonologists or physiotherapists. Conclusion: Although rare, Pompe disease should be considered in patients with proximal paresis and respiratory failure. More research into LOPD can help increasing precocity of diagnosis and treat it more effectively.